2002
DOI: 10.1144/1467-787302-021
|View full text |Cite
|
Sign up to set email alerts
|

An atmospheric pollution history for lead–zinc mining from the Ystwyth Valley, Dyfed, mid-Wales, UK as recorded by an upland blanket peat

Abstract: This paper presents records of the atmospheric deposition of lead and zinc close to a former metal mining area as recorded by an upland blanket peat that has accumulated on the northern slopes of the Ystwyth valley, Dyfed, mid-Wales, UK. The research objective was to explore the possibility that the peat contained a geochemical record of the pollution generated by mining activity during the last four millennia. Four monoliths were extracted from the blanket peat to reconstruct the pollution history of lead and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…Studies have shown that peat soils close to urban and industrial areas can be enriched by TEs through atmospheric deposition (Shuttleworth et al, 2014); in addition, the metal complexation capacity of organic matter makes peat an important Pb scavenger (Farmer et al, 2005;Hosseinpur and Motaghian, 2015). There have been no studies in Brazil that quantify the levels of TEs in the peat used for organic-mineral fertilizers; however, data from the international literature have shown that high concentrations of trace elements, especially Pb, can be found in peat (Mighall et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that peat soils close to urban and industrial areas can be enriched by TEs through atmospheric deposition (Shuttleworth et al, 2014); in addition, the metal complexation capacity of organic matter makes peat an important Pb scavenger (Farmer et al, 2005;Hosseinpur and Motaghian, 2015). There have been no studies in Brazil that quantify the levels of TEs in the peat used for organic-mineral fertilizers; however, data from the international literature have shown that high concentrations of trace elements, especially Pb, can be found in peat (Mighall et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…5). Roman lead pollution is common across the British Isles and in Europe (Mighall et al, 2002b;Bindler, 2006). The source of lead pollution at Borth Bog appears to be from a recently discovered local 1st century AD Roman smelting complex on the fringe of the Bog close to Erglodd Farm and approximately 500 m from the Flavian period Erglodd Roman Fort (Page, 2005;Timberlake, 2006).…”
Section: Romanmentioning
confidence: 99%
“…Mighall et al, 2002a). However, once the integrity of the metals in peat are established, these geochemical archives offer the opportunity to provide evidence of early metal mining in areas devoid of unequivocal or fragmentary archaeological and historical documentary evidence and to reconstruct atmospheric pollution histories since the advent of metalworking (Mighall et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, significant stores of Pb exist in the nearsurface layer of many peatland sites around the world (e.g. Shotyk et al, 2000;Vile et al, 2000;Mighall et al, 2002;Farmer et al, 2005;Rothwell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%